High refractive index and flame retardancy of epoxy thermoset cured by tris (2- mercaptoethyl) phosphate. (July 2016) - Luo, Chaoyun; Zuo, Jiandong; Wang, Fuquan; Yuan, Yanchao; Lin, Feng; Huang, Haohao; Zhao, Jianqing
Abstract: A novel curing agent containing phosphorus and sulfur, tris(2- mercaptoethyl) phosphate (TMEP), was designed and synthesized for LED packaging epoxy resin with high refractive index and good flame retardancy. The curing agent was prepared by sodium hydrosulfide method based on tris (2-chloroethyl) phosphate (TCEP) and sodium hydrosulfide. TMEP was mixed with triethylenetetramine and epoxy prepolymer at a certain ratio to generate cured samples. Fourier transform infrared spectroscopy (FTIR) and proton nuclear magnetic resonance (NMR) were employed to characterize the structure of the curing agent. The flame retardancy of the cured epoxy resin was determined by vertical burning test (UL-94) and limiting oxygen index (LOI) test. Its optical performance was examined by photoelectric haze meter and Abbe refractometer. The cured samples containing 21.6 wt% TMEP had UL-94 V0 rating and the LOI value of 29.2%. The results of scanning electron microscopy (SEM) and TGA demonstrated that TEMP could promote the formation of compact and continuous char foam layer during the combustion of the cured epoxy resin. The cured product containing 32 wt% TMEP yielded a light transmittance up to 92% and a refractive index as high as 1.593.